The Final of the Singspiel Doktor and Apotheker by Dittersdorf and the Tradition ofthe Opera Buffa - Svetlana B. Bubeeva (Современные проблемы музыкознания)
Doktor and Apotheker, a singspiel by Dittersdorf, is one of the most successful and popular operas of the 18th century. Many researchersclaim that the reason for its popularity is the “chain finale” that was first introduced by the composer. During the theatre reformation under the reign of Joseph II, German opera did not have its own models of final scenes to complete the acts. Dittersdorf was one of the pioneer composers who first applied Italian models to a singspiel. The finale is one of the central scenes in opera buffa demonstrating sophisticated dramatic situations and original music solutions. The article compares the final of the first act of Doktor and Apotheker and central finals of Mozart’s Le Nozze di Figaro as well as Dittersdorf’s Italian opera Democrito Corretto. The detailed analysis of the dramatic line, the structure of final scenes and means of expression shows that the opera embraces Italian traditions on different levels: from plots and characters to specific musical means. All of them make an organic contribution to the traditions of singspiel. Dittersdorf’s new approach to the opera finale laid the foundation for future generations of Austrian and German composers.